VD_FINDINFO HC / 2016 / 394 vom 24. März 2016 - VD Tribunal cantonal (2016)
BAIL À LOYER, RÉSILIATION, RÉNOVATION D'IMMEUBLE, PRINCIPE DE LA BONNE FOI | 271 al. 1 CO, 271 CO, 271a CO, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH)